2020
DOI: 10.14393/bj-v36n2a2020-46413
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the pineapple sweet orange on different rootstocks

Abstract: This study aimed at evaluating the agronomical performance of ‘Pineapple’ sweet orange grafted on ten rootstocks, in 2011-2017 harvests, so as to recommend the best combinations to be commercially explored in citrus growing regions in Bahia and Sergipe states, Brazil. An experiment was installed to test ten rootstock for 'pineapple' sweet orange: 'Santa Cruz' Rangpur lime, 'Red Rough' Lemon, 'Orlando' Tangelo, 'Sunki Tropical' Mandarin, 'Swingle' citrumelo, the citrandarins 'Indio' and 'Riverside' and the hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Overall, the varieties reached peak yields in the fifth harvest, and subsequently decreased. The same pattern was observed for 'Sincora,' 'Valencia Tuxpan,' and 'Pineapple' sweet oranges in the same study region (Carvalho et al, 2019 a;Martins et al, 2020). As the experimental orchard was cultivated under rainfed conditions, predominantly negative yearly water bal ances possibly interfered with the productive poten tial of the different varieties.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Overall, the varieties reached peak yields in the fifth harvest, and subsequently decreased. The same pattern was observed for 'Sincora,' 'Valencia Tuxpan,' and 'Pineapple' sweet oranges in the same study region (Carvalho et al, 2019 a;Martins et al, 2020). As the experimental orchard was cultivated under rainfed conditions, predominantly negative yearly water bal ances possibly interfered with the productive poten tial of the different varieties.…”
Section: Discussionsupporting
confidence: 70%
“…Lower yields in northeastern Brazil stem mainly from soils with fertility restrictions and hardsetting layers that impair drainage and root development in addition to water deficits due to irregular rainfall dis tribution, low technology adoption, improper man agement practices, and aging plants (Gomes et al, 2017;Carvalho et al, 2020;Martins et al, 2020). Despite water deficit negatively affecting citrus yields, citriculture in Brazil is predominantly rainfed (Carvalho et al, 2019(Carvalho et al, a, 2020(Carvalho et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the effect of citrus rootstocks on tree growth [11,[32][33][34]. In fact, substandard, semi-dwarfing, and dwarfing citrus rootstocks are known [35].…”
Section: 'Lane Late' Navel Orange Trees Sizementioning
confidence: 99%
“…The rootstock/scion diameter ratio is an indicator of the equality in growth rate between rootstock and scion (cultivar), so the difference among diameters may be an incompatibility measure [34].…”
Section: 'Lane Late' Navel Orange-rootstock Affinitymentioning
confidence: 99%
“…The previous works have shown that citrus rootstocks impact inversely on scion growth such as environmental and soil conditions (Forner-Giner et al, 2014;Chahal and Gill, 2015). The chosen of appropriate graft is essential for the production of fruits because of effects physiological both scion and rootstock relations of each other (Sharma et al, 2015), minerals uptake (Toplu et al, 2012 andHayat et al, 2019), vigor and yield behavior (Mallick et al, 2019 andMartins et al, 2020).…”
Section: Introductionmentioning
confidence: 99%